Bangladesh: GrameenPhone - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Grameen Village Phone programme is bringing connectivity to the rural areas of Bangladesh, enabling Grameen Bank´s borrowers to retail telephone services in their villages, and has the potential to penetrate the rural areas rapidly and effective